JURISDICTION OF SHOOTING DOWN UKRAINIA PLANE BY IRAN IN INTERNATIONAL LAW - Muhamad Rizky Ariyanto; Mohammad Abdullah Masrur; Alanda Aldora Lamadiri; Joanvie Alyssa Putri; Abhela Maulidea Putri Nyauko (International Journal of Law and Legal Ethics, 2023)
As we know, international civil aviation security standards are needed to keep flights safe and under control because aviation developments often involve crossing national borders.  Therefore, the 1944 Chicago Convention established the International Civil Aviation Organization or ICAO which is the International Civil Aviation Organization which falls under the standard rules and practices of the Chicago Convention.  In January 2020, the Iranian military fired its missiles at an international civilian aircraft with the aircraft code PS752.  That year was a year of mourning for the aviation world, due to the shelling by the Iranian military.  According to Underdal, based on the theory of International Regime Effectiveness.  This writing aims to determine the role of the ICAO Regime in handling the shooting case of PS752.  The result of this analysis is the effectiveness of ICAO as an international regime for international civil aviation.  In this paper the author uses a normative juridical methodology.